The impact of banking behaviour on monetary strategy in Europe - Manfred Borchert (Intereconomics, 2009)
Over the last twenty years, the process of European integration, and improvements in the processing and transmission of information, have meant that the European financial system has become less bank-based and more market-based. This trend has been reinforced by the transition to a single European currency. European banks are now increasingly expanding into asset management as well as the consulting business. What are the consequences of this for the effectiveness of European monetary policy? How should the ECB react?
Keywords: 330